KNOWLEDGE, ATTITUDE, AND PERCEPTION TOWARDS SOCIAL HEALTH INSURANCE AND ASSOCIATED FACTORS AMONG HEALTH PROFESSIONALS WORKING AT PUBLIC HEALTH FACILITIES IN GONDAR CITY, NORTH WEST ETHIOPIA - Bayan , Rita; Dwain, Brian; Target , Roy (American Journal of Public Health and Epidemiology (AJPHE), 2024)
Willingness to pay for and accept social health insurance varies across regions due to differences in knowledge, attitudes, and perceptions among employees. Ethiopia has introduced a social health insurance scheme despite facing challenges in its acceptance by the formal sector. However, little is known about the knowledge, attitudes, and perceptions of social health insurance. Therefore, this study aimed to assess the knowledge, attitudes, and perceptions regarding social health insurance and its associated factors among health professionals at public health facilities in Gondar City, Northwest Ethiopia. A facility-based cross-sectional and phenomenological design was used in this study. Four hundred and twenty-two participants and two focus group discussions were included for the quantitative and qualitative studies, respectively. A self-administered questionnaire and a focus group guide were used for data collection. Participants were selected using purposive and stratified simple random sampling techniques. EPI Data and Open Code software were used for data coding and entry, and the data was then exported to SPSS for analysis. Binary logistic regression and thematic analysis were used for quantitative and qualitative analysis, respectively. The results of the study suggested that knowledge and attitudes towards social health insurance were inadequate and unfavorable, despite positive perceptions found through quantitative analysis. Additionally, the qualitative findings suggested that knowledge, attitude, and perception were all poor. These findings highlight the need for targeted interventions to improve understanding and acceptance of social health insurance and to address negative attitudes towards it. By doing so, we can work towards increasing access to healthcare services and financial protection for individuals and families